Performance evaluation of identity-based encryption (IBE) remote attestation protocol in wireless sensor networks / Roszainiza Rosli - Rosli, Roszainiza (2014)
Remote attestation is a trusted computing activity which aims at establishing integrity of systems in a network. Therefore, remote attestation is important to be applied in Wireless Sensor Networks (WSNs) due to exposed nature of WSNs. However, to apply attestation on WSN will lead to high computation costs. Hence, efficient energy management is crucial since sensor nodes are resource constrained devices. This research was conducted with the main objective of evaluating the performance of Identity-Based Encryption (IBE) remote attestation protocol. The study involves two major parts i.e., the theoretical calculation and test-bed implementation of an IBE-Trust attestation. A comprehensive performance analysis of IBE-Trust attestation had been shown in this thesis by validating it with existing protocol and by comparing it between theoretical performance and real world implementation. Theoretical calculation was done based on XBee payload specification on diffirent input of data size regarding on the protocol. The real world implementation was carried out in the Wireless Laboratory at Faculty Electrical Engineering where a test bed consists of a sensor node and a base station connecting wirelessly through Xbee 802.15.4. As a result, on real world implementation, IBE-Trust shows a comparable performance between existing protocol and theoretical calculation.The work done in this thesis can be a benchmark for future performance comparison in different size of network, communication or others.